Strategy of Medical Care for Pregnant Women with Congenital Heart Disease - S. O. Siromakha; Yu. V. Davydova; A. O. Tarnavska; N. I. Volkova; N. B. Nakonechna (Ukrainian Journal of Cardiovascular Surgery, 2021)
Grown-up congenital heart (GUCH) is a global challenge nowadays. The strategy of medical care for GUCH women dur-ing pregnancy, childbirth and the postpartum period is a topic of active discussion in the expert community. These patients have significantly increased risk of maternal and perinatal loss. A national obstetric cardiology and cardiac surgery multi-disciplinary team (OCCS) established in academic institutions in 2013 has provided medical support to 896 GUCH pregnant women over the last 7 years. In total, GUCH patients accounted for 36% of the cohort of all the examined pregnant women. Of these, 474 (53%) were primigravid. The mean age of the patients at the time of the first visit was 27.3 ± 5.7 years. Patients with uncorrected CHD accounted for 66.2% (n = 593), and 33.8% (n = 303) of pregnant women had undergone correction, including hemodynamic correction of complex CHD in 5 patients. Risk stratification was performed using several scores (mWHO, ZAHARA, CARPREG) for the comprehensive assessment of cardiovascular risk and prediction of pregnancy, deliv-ery, and postpartum period course. 82 patients were classified as having high cardiovascular risk (CVR) after the stratifica-tion. They needed admission to the cardiac surgery facility to receive different types of medical care. There were 2 (2.4%) cases of maternal loss and 3 (3.8%) cases of adverse perinatal outcomes in this group of patients. The article presents the algorithms for multidisciplinary care strategy choice in GUCH pregnant women with high CVR and their routing principles developed by the OCCS. These algorithms significantly reduced adverse outcomes of pregnancy and childbirth in this group of patients. Long-term results were evaluated in 69 patients (86.3%). The follow-up period ranged from 1 to 91 months, on average 34.4 ± 23.6 months. There were no long-term maternal losses or repeated cardiac surgeries. There was one case of unexplained death of a child 8 months after birth. The strategy of multidisciplinary medical care of a high-class GUCH pregnant woman should be personalized depending on the clinical data and in accordance with the ESC 2018 guidelines.